Biocontrol potential of Pseudomonas protegens ML15 against Botrytis cinerea causing gray mold on postharvest tomato (Solanum lycopersicum var. cerasiforme) - Ajijah, Nur; Fiodor, Angelika; Dziurzynski, Mikolaj; Stasiuk, Robert; Pawlowska, Julia; Dziewit, Lukasz; Pranaw, Kumar (Frontiers in Plant Science, 2023)
Gray mold, caused by Botrytis cinerea is a major cause of post-harvest rot of fresh fruits and vegetables. The utilization of selected microorganisms as biocontrol agents is a promising alternative to effectively control gray mold on tomatoes. The current study was conducted to explore potential biocontrol mechanisms of the Pseudomonas strain to control infections on post-harvest tomatoes. Among the 8 tested bacterial isolates, Pseudomonas protegens ML15 demonstrated antagonistic activity to Botrytis cinerea. Moreover, P. protegens ML15 exhibited the production of siderophores, hydrogen cyanide, ammonia, exopolysaccharides, lipase, biosurfactant, 2,4-diacetylphloroglucinol, and several other antifungal compounds also, such as 1-tetradecanol, cyclododecane, 2,4-di-tert-butylphenol, and 2-methyl-1-hexadecanol. A comprehensive genomic analysis of P. protegens ML15 unravels 18 distinct genetic regions with the potential for biosynthesizing secondary metabolites, known for their pivotal role in biocontrol responses against plant pathogens. In vivo, experiments showed that both culture suspension and cell-free supernatant of P. protegens ML15 significantly reduced fungal growth (53.0 ± 0.63 %) and mitigated disease development (52.8 ± 1.5 %) in cherry tomatoes at four days post-B. cinerea inoculation. During the infection, the application of P. protegens ML15 resulted in the augmentation of total antioxidant, phenolic content, and ascorbic acids content. Thus, our results suggested that P. protegens ML15’s role as a biocontrol agent against B. cinerea-induced postharvest tomato decay achieved through the secretion of antifungal substances, induction of tomato defense responses, and inhibition of mycelial growth of B. cinerea. These findings provide a significant contribution to the ongoing search for alternative, eco-friendly methods of controlling gray mold in fresh products. The utilization of P. protegens ML15 as a biocontrol agent could help to reduce the reliance on chemical fungicides and promote sustainable agriculture practices.